ATP and repetitive electric stimulation increases leukemia inhibitory factor expression in astrocytes: A potential role for astrocytes in the action mechanism of electroconvulsive therapy. Issue 5 (5th March 2020) - Maruyama, Soichiro; Boku, Shuken; Okazaki, Satoshi; Kikuyama, Hiroki; Mizoguchi, Yoshito; Monji, Akira; Otsuka, Ikuo; Sora, Ichiro; Kanazawa, Tetsufumi; Hishimoto, Akitoyo; Yoneda, Hiroshi
Abstract : Aim: Electroconvulsive therapy (ECT) is effective for psychiatric disorders. However, its action mechanism remains unclear. We previously reported that transcription factor 7 (TCF7) was increased in patients successfully treated with ECT. TCF7 regulates Wnt pathway, which regulates adult hippocampal neurogenesis. Adult hippocampal neurogenesis is involved in the pathophysiology of psychiatric disorders. Astrocytes play a role in adult hippocampal neurogenesis via neurogenic factors. Of astrocyte‐derived neurogenic factors, leukemia inhibitory factor (LIF) and fibroblast growth factor 2 (FGF2) activate Wnt pathway. In addition, adenosine triphosphate (ATP), released from excited neurons, activates astrocytes. Therefore, we hypothesized that ECT might increase LIF and/or FGF2 in astrocytes. To test this, we investigated the effects of ATP and electric stimulation (ES) on LIF and FGF2 expressions in astrocytes. Methods: Astrocytes were derived from neonatal mouse forebrain and administered ATP and ES. The mRNA expression was estimated with quantitative reverse‐transcription polymerase chain reaction. Protein concentration was measured with ELISA. Results: ATP increased LIF, but not FGF2, expression. Multiple ES, but not single, increased LIF expression. Knockdown of P2X2 receptor (P2X2R) attenuated ATP‐induced increase of LIF mRNA expression. In contrast, P2X3 and P2X4 receptors intensified it. Conclusion: P2X2R may mediate ATP‐induced LIF expression in astrocytes and multiple ES directly increases LIF expression in astrocytes. Therefore, both ATP/P2X2R and multiple ES‐induced increases of LIF expression in astrocytes might mediate the efficacy of ECT on psychiatric disorders. Elucidating detailed mechanisms of ATP/P2X2R and multiple ES‐induced LIF expression is expected to result in the identification of new therapeutic targets for psychiatric disorders.